Khataman Al-Qur'an di Kuburan Malam Jum'at Legi: Analisis Spiritual dan Sosial di Desa Montorna - Sri Wahyuni; Mawaddatul Jannah; Fadiah Alfi Laila; Zaimatus Sholikhah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Quranic recitation (Khataman Al-Qur'an) at the cemetery on the night of Friday Legi in Montorna Village, Pasong-Songan, Sumenep, reflects the close relationship between culture and society as the foundation of civilization. This study aims to comprehensively reveal how the tradition of Quranic recitation at the cemetery on the night of Friday Legi demonstrates the integration of religious and social aspects in the life of the Montorna community. This research adopts a qualitative method with a descriptive and phenomenological approach. The study finds that the tradition of Quranic recitation functions not only as a means of enhancing the community's spirituality but also as a platform for social interaction that strengthens relationships among residents. The implication of this study emphasizes the importance of understanding local traditions to reinforce the religious and social values of the community, as well as how traditions can serve as a medium for maintaining and strengthening social cohesion within society.